Timing of Antiretroviral Therapy for HIV in the Setting of TB Treatment - Damani A. Piggott; Petros C. Karakousis (Clinical and Developmental Immunology)
The convergent human immunodeficiency virus (HIV) and tuberculosis (TB) pandemics continue to collectively exact significant morbidity and mortality worldwide. Highly active antiretroviral therapy (HAART) has been a critical component in combating the scourge of these two conditions as both a preemptive and therapeutic modality. However, concomitant administration of antiretroviral and antituberculous therapies poses significant challenges, including cumulative drug toxicities, drug-drug interactions, high pill burden, and the immune reconstitution inflammatory syndrome (IRIS), thus complicating the management of coinfected individuals. This paper will review data from recent studies regarding the optimal timing of HAART initiation relative to TB treatment, with the ultimate goal of improving coinfection-related morbidity and mortality while mitigating toxicity resulting from concurrent treatment of both infections.